2014
DOI: 10.1038/ncomms4200
|View full text |Cite
|
Sign up to set email alerts
|

Integration of molecular and enzymatic catalysts on graphene for biomimetic generation of antithrombotic species

Abstract: The integration of multiple synergistic catalytic systems can enable the creation of biocompatible enzymatic mimics for cascading reactions under physiologically relevant conditions. Here we report the design of a graphene–haemin–glucose oxidase conjugate as a tandem catalyst, in which graphene functions as a unique support to integrate molecular catalyst haemin and enzymatic catalyst glucose oxidase for biomimetic generation of antithrombotic species. Monomeric haemin can be conjugated with graphene through π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 47 publications
0
72
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] With the ultimate goal of achieving fast, sensitive, large-scale, and low-cost molecular analysis, aw ide variety of detection technologies have been developed, such as fluorescent, [14] spectroscopic, [15] electrical, [16] magnetic, [17] and mechanical methods. [1][2][3][4][5][6][7][8][9][10][11][12][13] With the ultimate goal of achieving fast, sensitive, large-scale, and low-cost molecular analysis, aw ide variety of detection technologies have been developed, such as fluorescent, [14] spectroscopic, [15] electrical, [16] magnetic, [17] and mechanical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] With the ultimate goal of achieving fast, sensitive, large-scale, and low-cost molecular analysis, aw ide variety of detection technologies have been developed, such as fluorescent, [14] spectroscopic, [15] electrical, [16] magnetic, [17] and mechanical methods. [1][2][3][4][5][6][7][8][9][10][11][12][13] With the ultimate goal of achieving fast, sensitive, large-scale, and low-cost molecular analysis, aw ide variety of detection technologies have been developed, such as fluorescent, [14] spectroscopic, [15] electrical, [16] magnetic, [17] and mechanical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the reactive groups of GO facilitate chemical interaction and conjugation with an extensive variety of molecules [40, 7882]. There are already limited data that graphene and especially GO have a great potential in becoming such a drug-eluting delivery system that can reduce endothelial proliferation and restenosis in grafts [22, 26, 27, 33, 83]. A study on the release of anti-inflammatory medication by carbon coating is of relevance to abdominal aortic aneurysm (AAA) repair and the postimplantation syndrome [84].…”
Section: Discussionmentioning
confidence: 99%
“…Weaver et al developed a GO-based delivery system controlled by electrical impulses to release dexamethasone into the bloodstream [30]. Other studies have reported the transport and release of antithrombotic agents by graphene [31, 32]. …”
Section: Special Characteristics Of Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28] Noble metal graphene composites have been widely explored for chemical reactions, with improved catalytic activity and enhanced durability. [24][25][26][27][28] Noble metal graphene composites have been widely explored for chemical reactions, with improved catalytic activity and enhanced durability.…”
Section: Introductionmentioning
confidence: 99%